Stress Dissipation Encoded Silk Fibroin Electrode for the Athlete‐Beneficial Silk Bioelectronics (Adv. Sci. 8/2022). Issue 8 (15th March 2022) - Choi, Woojin; Heo, Deokjae; Kim, Taeho; Jung, Sungwon; Choi, Moonhyun; Heo, Jiwoong; Kwon, Jae‐Sung; Kim, Byeong‐Su; Lee, Wonhwa; Koh, Won‐Gun; Cho, Jeong Ho; Lee, Sangmin; et al.
Abstract : Wearable Bioelectronics Wearable bioelectronics pursues superior biopolymer fabric enduring mechanical stress during workouts. In article number 2105420, Sangmin Lee, Jinkee Hong, and co‐workers develop a super‐tough silk fibroin fabric band by encoding the domains for stress dissipation. Precisely crosslinked phenolic amino acid offers sufficient toughness exceeding the fitness‐originated fabric deformations. Furthermore, the proposed silk bioelectronics can assist the active workouts by relieving muscular fatigue and injuries.